Co-infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and human coronavirus HKU1 (HCoV-HKU1) - Laszlo Madaras; Radean Anvari; Claudia Schuchardt-Peet; Abhinav Hoskote; Rahul Kashyap (European Journal of Case Reports in Internal Medicine)
Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and human coronavirus HKU1 (HCoV-HKU1) are two forms of human coronaviruses known to cause respiratory tract symptoms. A co-infection with both viruses is rare, particularly in the United States. Case description: An 85-year-old male presented to the Emergency Department with recurrent falls, diarrhoea and cough, and whose viral panel was positive for both SARS-COV-2 and HCoV-HKU1. The patient developed bacterial pneumonia and was treated with antibacterial agents and glucocorticoids. His past medical history of atrial fibrillation required careful monitoring and subsequent discontinuation of remdesivir, a medication known to cause adverse cardiovascular effects in COVID-19 patients. The length of stay was also prolonged due to delirium and deconditioning. Ultimately, the patient required an urgent ablation followed by the placement of a permanent pacemaker, and anticoagulation therapy was initiated before discharge. The patient had a favourable outcome given the rarity of this case. Discussion: COVID-19 patients co-infected with other human coronaviruses should be monitored for disease progression and superimposed bacterial infections. Providers should be cautious with the use of remdesivir in cases of co-infection and in severely ill COVID-19 patients who have a history of atrial fibrillation.